High-flame-retardant plate and production process thereof

By using a modified polyvinyl alcohol-to-nano calcium carbonate crosslinking network and a modified borax esterification-chelation structure, combined with a basalt fiber three-dimensional reinforcing skeleton, the problems of uneven flame retardant dispersion and insufficient mechanical properties in traditional flame-retardant boards have been solved, achieving the production of highly efficient flame-retardant and high-strength boards.

CN121063906AActive Publication Date: 2025-12-05JIANGSU MEIBIAO HOME TECH CO LTD

Patent Information

Application Number
CN202511291418.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-10
Publication Date
2025-12-05
Estimated Expiration
2045-09-10

AI Technical Summary

Technical Problem

Traditional flame-retardant boards suffer from uneven dispersion of flame retardants, poor compatibility with substrates, and insufficient mechanical properties. Furthermore, the production process makes it difficult to achieve uniform dispersion of raw materials and control of slurry viscosity, resulting in performance fluctuations and short service life.

Method used

A cross-linked network is formed by modified polyvinyl alcohol and nano-calcium carbonate, and a highly efficient flame-retardant synergistic network is formed by modified borax, nano-zinc borate, and chlorinated paraffin-70. A three-dimensional reinforcing skeleton is constructed by combining basalt fiber. By precisely controlling process parameters such as stirring speed, temperature, and pressure, the flame-retardant components are uniformly dispersed and the density of the board is ensured.

Benefits of technology

It achieves uniform dispersion of flame-retardant components in the substrate, improves the flame-retardant properties, flexural strength and toughness of the board, reduces quality fluctuations during the production process, extends service life and improves water resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a high-flame-retardant plate and a production process thereof, and relates to the technical field of flame-retardant materials. The high-flame-retardant plate is prepared from the following raw materials in parts by weight: 90 to 110 parts of magnesium oxide, 15 to 20 parts of magnesium chloride, 30 to 35 parts of magnesium sulfate, 1.5 to 3 parts of modified polyvinyl alcohol, 1 to 2 parts of starch, 0.3 to 0.8 part of modified borax, 0.2 to 0.5 part of silane coupling agent KH-550, 1 to 2 parts of absolute ethyl alcohol, 2.5 to 3.5 parts of nano zinc borate, 2 to 4 parts of chlorinated paraffin-70, 0.5 to 1 part of nano titanium dioxide, 5 to 10 parts of basalt fiber and 0.2 to 0.5 part of calcium stearate. And 90 to 110 parts of deionized water. The raw materials of the high-flame-retardant plate are subjected to condensation cross-linking and nanometer enhancement of the modified polyvinyl alcohol and esterification and chelation treatment of the modified borax, so that the flame-retardant compatibility is improved. In production, pre-dispersion of the silane coupling agent and synergistic mixing of the starch paste are matched with precise viscosity regulation and control and stepped sanding, so that uniformity of the slurry is ensured. And hot pressing parameters are optimized, so that the plate is high in density and excellent in flame retardance and surface precision.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of flame-retardant materials, in particular to a high-flame-retardant plate and a production process thereof. BACKGROUND

[0002] In the fields of construction, furniture and rail transportation, the flame-retardant performance of a plate is one of the core indicators for ensuring safety. Traditional plates mostly rely on wood and plastic substrates, which have poor flame-retardant performance, are easy to burn when exposed to fire and release toxic smoke, posing a serious safety hazard. Although existing flame-retardant plates have improved performance by adding flame retardants, they generally have low flame-retardant efficiency, poor mechanical properties and insufficient processing stability.

[0003] Currently commonly used flame retardants such as zinc borate and chlorinated paraffin are not uniformly dispersed in the substrate, which can easily lead to fluctuations in the flame-retardant performance of the plate, and excessive addition can reduce the strength and toughness of the material. When unmodified, additives such as polyvinyl alcohol and borax have poor compatibility with inorganic substrates, which can easily cause delamination and cracking, affecting the service life of the plate.

[0004] In terms of production process, traditional stirring and mixing methods cannot achieve uniform dispersion of raw materials, and improper control of slurry viscosity can lead to uneven coating. During the hot pressing process, one-step heating can easily cause internal stress concentration, resulting in deformation or insufficient density of the plate. In addition, if the length and diameter of reinforcing materials such as basalt fibers are not controlled well, they not only cannot play a reinforcing role, but also can become stress weak points, reducing the mechanical properties of the plate.

[0005] In the prior art, magnesium chloride and magnesium sulfate are directly dry-mixed and added to the system, and a high-magnesium chloride and low-magnesium sulfate ratio is often used. Although this can quickly form strength, a high content of magnesium chloride can easily cause the plate to absorb moisture and return to halogen, and salt frost and water droplets can easily appear on the surface in a high-humidity environment, affecting the service life and aesthetics. At the same time, the concentration of the salt solution is not controlled, further exacerbating performance fluctuations. SUMMARY

[0006] To overcome the shortcomings of the prior art, the present application provides a high-flame-retardant plate and a production process thereof, which solves the problems of uneven dispersion of flame retardants, poor compatibility of substrates and insufficient mechanical properties of traditional flame-retardant plates.

[0007] To achieve the above purpose, the present application realizes the following technical solutions: A kind of high flame-retardant board, comprising the following raw materials by weight: 90-110 parts of magnesium oxide, 15-20 parts of magnesium chloride, 30-35 parts of magnesium sulfate, 1.5-3 parts of modified polyvinyl alcohol, 1-2 parts of starch, 0.3-0.8 parts of modified borax, 0.2-0.5 parts of silane coupling agent KH-550, 1-2 parts of anhydrous ethanol, 2.5-3.5 parts of nano zinc borate, 2-4 parts of chlorinated paraffin-70, 0.5-1 parts of nano titanium dioxide, 5-10 parts of basalt fiber, 0.2-0.5 parts of calcium stearate, 90-110 parts of deionized water.

[0008] Further, the length of the basalt fiber is 3-5 mm, and the diameter is 10-15 μm. The basalt fiber of this size can be uniformly dispersed in the substrate to construct a three-dimensional reinforcing skeleton, which not only avoids uneven dispersion caused by too long fibers, but also prevents ineffective stress transmission caused by too short fibers, and cooperates with the modified polyvinyl alcohol to improve the bending strength and toughness of the board and reduce stress weak points.

[0009] Further, the modified polyvinyl alcohol is prepared according to the following steps: A1, take polyvinyl alcohol powder and add it to a three-necked flask, then add deionized water and place it in a 70℃ constant temperature water bath, stir at a speed of 300 rpm for 40 min until the polyvinyl alcohol is fully swollen; by heating, the intermolecular force of the polyvinyl alcohol molecular chain is weakened, and water molecules penetrate into the chain to achieve full swelling, providing a uniform system for subsequent reactions; then add sodium dodecyl sulfate and continue to stir at a speed of 300 rpm for 20 min to improve the dispersibility of the polyvinyl alcohol; then slowly add glacial acetic acid with a dropper, stirring while adding, adjust the pH value of the system to 5.5 to provide suitable catalytic conditions for the subsequent condensation and cross-linking reaction of glutaraldehyde and the hydroxyl group of polyvinyl alcohol, and stir for 15 min to obtain a pretreated polyvinyl alcohol solution; A2, under the condition of 300 rpm stirring, add ethylene glycol to the pretreated polyvinyl alcohol solution and stir for 10 min; ethylene glycol acts as a chain extender, its hydroxyl group interacts with the hydroxyl group on the polyvinyl alcohol molecular chain to provide more active sites for cross-linking reaction; then add glutaraldehyde in 3 portions, with an interval of 5 min after each addition, adjust the water bath temperature to 50℃, and continue to stir at a speed of 250 rpm for 40 min; the aldehyde group of glutaraldehyde reacts with the hydroxyl group of polyvinyl alcohol at 50℃ to form stable ether bonds or hemiacetal structures, and a three-dimensional cross-linked network is constructed; turn off the water bath heating and allow the solution to cool naturally to room temperature; A3, under the condition of 300 rpm stirring, add titanate coupling agent into the reaction system after the second modification, stir for 15 min, the titanate coupling agent reacts with the hydroxyl group on the surface of nano calcium carbonate through the alkoxy group in its molecule to form chemical bonding, and the other end of the organic group interacts with the hydroxyl group of the polyvinyl alcohol molecular chain, thereby improving the interfacial compatibility of nano calcium carbonate and polyvinyl alcohol; then add nano calcium carbonate, increase the stirring speed to 400 rpm, and continuously stir at room temperature for 30 min to obtain modified polyvinyl alcohol; through the nano enhancement effect, further improve the mechanical properties of polyvinyl alcohol and the compatibility with inorganic substrates.

[0010] Further, the amount ratio of polyvinyl alcohol powder, deionized water, sodium dodecyl sulfate and glacial acetic acid in A1 is 15 g: 150 mL: 0.5 g: 3 mL; wherein the polyvinyl alcohol is type 1788, with appropriate polymerization degree and alcoholysis degree, to ensure swelling and reactivity.

[0011] Further, the amount ratio of ethylene glycol and glutaraldehyde in A2 is 5 mL: 2 mL.

[0012] Further, the amount ratio of titanate coupling agent and nano calcium carbonate in A3 is 1 mL: 2 g.

[0013] Further, the modified borax is prepared according to the following specific steps: B1, dissolve borax in distilled water and place it in a 50℃ constant temperature water bath, stir at a speed of 200 rpm until the borax is completely dissolved, then continue to stir at the same temperature and speed for 30 min, the borax is hydrolyzed to generate boric acid and borate ions in the 50℃ water bath; then slowly add glycerol, adjust the stirring speed to 250 rpm, and continue to stir at 50℃ water bath for 50 min to complete the esterification reaction, and then cool to room temperature naturally; glycerol reacts with boric acid through esterification reaction, the hydroxyl group of boric acid and the hydroxyl group of glycerol are dehydrated to form boric acid ester bond, and the organic compatibility of borax is improved by introducing organic groups, and the thermal stability of borax is enhanced by the ester bond structure; B2, add tartaric acid into the reaction system after the first modification, stir at a speed of 250 rpm for 15 min; then add citric acid in two times, each time interval is 10 min, and continue to stir at a speed of 250 rpm for 30 min after all the citric acid is added, to form a chelate structure; the chelate structure fixes boron element through strong coordination bond, avoids the loss of boron at high temperature, and enhances the synergistic effect with nano zinc borate, chlorinated paraffin-70 and other flame retardants; B3, under the condition of stirring at 300 rpm, polyethylene glycol was added into the second modified system, and stirred for 20 min; then hydroxypropyl methyl cellulose was added, and stirred at 300 rpm for 40 min at room temperature to obtain modified borax; polyethylene glycol was chelated with the active groups on the surface of the borax chelate through the hydroxyl groups thereof, so as to reduce the interfacial tension; hydroxypropyl methyl cellulose acted as a high molecular dispersant, and prevented the agglomeration of the borax chelate particles through the steric hindrance effect of the molecular chain; the synergistic effect of the two made the modified borax uniformly dispersed in the subsequent slurry, so as to avoid the fluctuation of the flame retardation performance caused by local aggregation, and improve the compatibility with the base material.

[0014] Further, the amount ratio of borax, distilled water and glycerol in B1 is 8 g:80 mL:6 mL.

[0015] Further, the amount ratio of tartaric acid and citric acid in B2 is 1.5 g:1 g.

[0016] Further, the amount ratio of polyethylene glycol and hydroxypropyl methyl cellulose in B3 is 3 mL:0.5 g.

[0017] Further, the citric acid is added in several times in B2, and is combined with tartaric acid to form a chelate structure, so as to ensure the thermal stability and flame retardation synergistic effect of borax.

[0018] A production process of a high flame-retardant board, specifically comprising the following steps: S1, silane coupling agent KH-550 and anhydrous ethanol were added into a container, stirred at 1300 rpm for 15 min, and stood for 30 min for standby; 80-90 DEG C deionized water was taken and added into the modified borax to be stirred until dissolved, then poured into the above-mentioned silane coupling agent diluent, stirred at 300 rpm in a 60-70 DEG C water bath for 15-20 min, and cooled for standby; deionized water was taken and added into a batching tank, stirred at 150 rpm and heated to 30-40 DEG C, first added with magnesium sulfate and stirred for 5 min, then added with magnesium chloride, after the addition, adjusted to 200 rpm and stirred for 25-35 min, until the salts were completely dissolved, to ensure that the magnesium chloride and magnesium sulfate salt complex water agent had a magnesium chloride degree of 22-28 Be°, then stood for 15 min to discharge the bubbles, and the batching tank was sealed for standby; the magnesium chloride and magnesium sulfate were pre-prepared into an aqueous solution with a magnesium chloride degree of 22-28 Be°, to ensure that the two kinds of salts were uniformly dispersed, to avoid the difference in dissolution during dry mixing, and to precisely control the salt concentration, to provide a stable environment for the full reaction of magnesium cement; S2, deionized water was poured into a reaction kettle, heated to 60-70 DEG C under stirring at 200 rpm, and slowly added with modified polyvinyl alcohol, and continuously stirred until completely dissolved; starch was mixed with deionized water, stirred at 400 rpm for 10-15 min to prepare a starch paste, poured into the above-mentioned solution, and stirred at 250 rpm for 30 min to obtain an organic modified glue solution; S3, dry magnesium oxide, nano zinc borate, chlorinated paraffin-70, nano titanium dioxide, basalt fiber and calcium stearate are added to a double shaft stirring mixer, and dry mixing is carried out at 300 rpm for 3-5 min; the organic modified glue solution prepared in S2, the salt compound water agent prepared in S1 and the pretreatment solution of S1 are added, and stirring is carried out at 200-300 rpm for 30-40 min until the slurry is uniform and particle-free, and the remaining deionized water is used to adjust the slurry viscosity to 2000-3000 cP; S4, the slurry is placed on the conveying belt of the coating machine, the gap is adjusted to make the coating amount , and a plate blank is formed; the blank is placed in a hot press, and hot pressing is carried out at 110-120 DEG C and 1.2-1.5 MPa, and the hot pressing time is each millimeter of plate thickness x 1.2 min; S5, the plate blank is naturally cooled to room temperature for 2-3 h, and 120 and 240 mesh step sanding is used to sand the surface to a roughness Ra≤1.6 μm, and a high flame-retardant plate is obtained.

[0019] Further, the hot pressing process in S4 uses a temperature of 110-120 DEG C and a pressure of 1.2-1.5 MPa, and the hot pressing time is controlled to be each millimeter of plate thickness x 1.2 min, so that a dense structure is formed in the plate, and the uniform distribution of the flame-retardant component is ensured, thereby obtaining excellent flame-retardant performance and dimensional stability.

[0020] The application provides a high flame-retardant plate and a production process thereof, and has the following beneficial effects: 1. The combination of the modified polyvinyl alcohol crosslinked structure and the nano calcium carbonate reinforcing system, the esterification-chelation synergistic structure of the modified borax, the nano zinc borate and the chlorinated paraffin-70 forms a high-efficiency flame-retardant synergistic network. The combination makes the flame-retardant components uniformly dispersed in the substrate, avoids the performance fluctuation caused by the local aggregation of traditional flame retardants, improves the bonding force between the flame-retardant components and the substrate through chemical bonding, ensures that the plate continuously plays a flame-retardant role in a high-temperature environment, effectively delays the burning speed and reduces the release of toxic smoke.

[0021] 2. The basalt fiber and the modified polyvinyl alcohol form a three-dimensional reinforcing skeleton, the crosslinked structure of the modified polyvinyl alcohol improves the bonding strength of the substrate, and the addition of calcium stearate improves the interface bonding state in the material. The synergistic effect of the three solves the problem of strength reduction of traditional flame-retardant plates caused by the addition of flame retardants, so that the plate has high bending strength and toughness, and reduces the risk of cracking and damage caused by stress during use.

[0022] 3、Silane coupling agent pre-dilution treatment enhances the compatibility of inorganic raw materials and organic additives, precise control of process parameters such as step-by-step stirring and gradient temperature rise ensures that the slurry is uniform and particle-free during mixing and coating, and the viscosity is stable within the range of 2000-3000 cP. The optimization of temperature, pressure and time of hot pressing process avoids internal bubbles and stress concentration of the board, combined with 120 and 240 mesh step sanding treatment, so that the finished board has high density and surface roughness Ra≤1.6μm, greatly reducing the quality fluctuations during production.

[0023] 4、Modified polyvinyl alcohol and borax form a stable chemical bond structure with inorganic materials such as magnesium oxide and magnesium chloride, improving the water resistance and aging resistance of the board. The corrosion resistance of basalt fiber and the photocatalytic activity of nano titanium dioxide work together to reduce the damage to the structure of the board in humid environments or long-term use, so that the board can maintain stable performance in various scenarios such as construction and furniture, prolonging the service life.

[0024] 5、By optimizing the ratio of low-magnesium chloride and high-magnesium sulfate, it can ensure that most of the magnesium chloride can effectively participate in the reaction to form an effective gel structure, thereby obtaining better strength development and higher final mechanical properties. Precise Baume degree salt solution is prepared in advance to fundamentally inhibit the transformation of 518 phase to 318 phase, greatly reducing the content of free chloride ions, not only solving the problem of moisture absorption and halogen return of the board, but also significantly improving the water resistance and dimensional stability of the board under long-term use, overcoming the biggest application obstacle of magnesium oxychloride cement materials. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present application will be described below. Obviously, the described embodiments are only a part of the embodiments of the present application, not all. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.

[0026] Embodiment 1, preparation of high flame-retardant board, the specific preparation steps are as follows: S1, 0.2 parts of silane coupling agent KH-550 and 1 part of anhydrous ethanol are added to a container, stirred at 1300 rpm for 15 min, and stand for 30 min for standby; another 12 parts of 80℃ deionized water is added to 0.3 parts of modified borax and stirred until dissolved, then poured into the above silane coupling agent dilution solution, stirred at 300 rpm in 60℃ water bath for 15 min, and cooled for standby; take 48 parts of deionized water and add it to the batching tank, stir at 150 rpm and heat to 30℃, first add 30 parts of magnesium sulfate and stir for 5 min, then add 15 parts of magnesium chloride, after adding, adjust to 200 rpm and stir for 25 min, until the salt is completely dissolved, then stand for 15 min to remove bubbles, seal the batching tank, and standby; S2, pour 18 parts of deionized water into the reaction kettle, heat to 60°C under 200 rpm stirring, slowly add 1.5 parts of modified polyvinyl alcohol, continue to stir until completely dissolved; mix 1 part of starch with 6 parts of deionized water, stir at 400 rpm for 10 min to make starch paste, pour into the above solution, stir at 250 rpm for 30 min to get organic modified glue solution; S3, add 90 parts of dry magnesium oxide, 2.5 parts of nano zinc borate, 2 parts of chlorinated paraffin-70, 0.5 parts of nano titanium dioxide, 5 parts of basalt fiber and 0.2 parts of calcium stearate into a double shaft stirring mixer, dry mix at 300 rpm for 3 min; add the organic modified glue solution prepared in S2, the salt compound water agent prepared in S1 and the pretreatment solution of S1, stir at 200 rpm for 30 min until the slurry is uniform and particle-free, adjust the slurry viscosity to 2000 cP with the remaining 6 parts of deionized water; S4, place the slurry on the conveying belt of the coating machine, adjust the gap to make the coating amount 165 g / m 2 , form a plate blank; put the blank into a hot press, hot press at 110°C, 1.2 MPa, hot pressing time per millimeter plate thickness x 1.2 min; S5, naturally cool the plate blank to room temperature for 2 h, sand with 120 and 240 mesh step sandpaper, sand to a surface roughness Ra≤1.6 μm, to get high flame retardant plate.

[0027] Example 2, preparation of high flame retardant plate, the specific preparation steps are as follows: S1, add 0.5 parts of silane coupling agent KH-550 and 2 parts of anhydrous ethanol into a container, stir at 1300 rpm for 15 min, stand for 30 min for standby; take another 14 parts of 90°C deionized water, add 0.8 parts of modified borax, stir until dissolved, pour into the above silane coupling agent diluent, stir at 300 rpm in 70°C water bath for 20 min, cool for standby; take 56 parts of deionized water into a batching tank, stir at 150 rpm and heat to 40°C, first add 35 parts of magnesium sulfate and stir for 5 min, then add 20 parts of magnesium chloride, after adding, adjust to 200 rpm stirring for 35 min, until the salts are completely dissolved, then stand for 15 min to release the bubbles, seal the batching tank for standby; S2, pour 18 parts of deionized water into the reaction kettle, heat to 60°C under 200 rpm stirring, slowly add 1.5 parts of modified polyvinyl alcohol, continue to stir until completely dissolved; mix 1 part of starch with 6 parts of deionized water, stir at 400 rpm for 10 min to make starch paste, pour into the above solution, stir at 250 rpm for 30 min to get organic modified glue solution; S3, 110 parts of dry magnesium oxide, 3.5 parts of nano zinc borate, 4 parts of chlorinated paraffin-70, 1 part of nano titanium dioxide, 10 parts of basalt fiber and 0.5 parts of calcium stearate were added into a double-shaft stirring mixer, and dry mixing was carried out at 300 rpm for 5 min; the organic modified glue solution prepared in S2, the salt compound water agent prepared in S1 and the pretreatment solution of S1 were added, and stirring was carried out at 300 rpm for 40 min until the slurry was uniform and particle-free, and the remaining 5 parts of deionized water was used to adjust the slurry viscosity to 3000 cP; S4, the slurry was placed on the conveying belt of the coating machine, the gap was adjusted to make the coating amount 175 g / m 2 , and a plate blank was formed; the blank was placed into a hot press, and hot pressing was carried out at 120℃ and 1.5 MPa, and the hot pressing time was every millimeter of plate thickness x 1.2 min; S5, the plate blank was naturally cooled to room temperature for 3 h, and 120 and 240 mesh step sanding was carried out, and the surface roughness Ra was ≤1.6 μm, and a high flame-retardant plate was obtained.

[0028] Example 3, preparation of high flame-retardant plate, the specific preparation steps are as follows: S1, 0.3 parts of silane coupling agent KH-550 and 1 part of anhydrous ethanol were added into a container, and stirring was carried out at 1300 rpm for 15 min, and standing was carried out for 30 min for standby; 13 parts of 85℃ deionized water was taken and 0.5 parts of modified borax was stirred until dissolved, and was poured into the above-mentioned silane coupling agent diluent, and stirring was carried out at 300 rpm in a 65℃ water bath for 17 min, and cooling was carried out for standby; 52 parts of deionized water was taken and added into a batching tank, and stirring was carried out at 150 rpm and heated to 35℃, and 32 parts of magnesium sulfate was first added and stirred for 5 min, and then 18 parts of magnesium chloride was added, and after completion, stirring was carried out at 200 rpm for 25-35 min until the salts were completely dissolved, and then standing was carried out for 15 min to remove bubbles, and the batching tank was sealed for standby; S2, 23 parts of deionized water was poured into a reaction kettle, and stirring was carried out at 200 rpm and heated to 65℃, and 2 parts of modified polyvinyl alcohol was slowly added, and continuous stirring was carried out until completely dissolved; 1 part of starch was mixed with 6 parts of deionized water, and starch paste was prepared by stirring at 400 rpm for 12 min, and was poured into the above-mentioned solution, and stirring was carried out at 250 rpm for 30 min, and an organic modified glue solution was obtained; S3, 100 parts of dry magnesium oxide, 3 parts of nano zinc borate, 3 parts of chlorinated paraffin-70, 0.7 parts of nano titanium dioxide, 7 parts of basalt fiber and 0.3 parts of calcium stearate were added into a double-shaft stirring mixer, and dry mixing was carried out at 300 rpm for 4 min; the organic modified glue solution prepared in S2, the salt compound water agent prepared in S1 and the pretreatment solution of S1 were added, and stirring was carried out at 250 rpm for 35 min until the slurry was uniform and particle-free, and the remaining 6 parts of deionized water was used to adjust the slurry viscosity to 2500 cP; S4, the slurry was placed on the conveying belt of the coating machine, the gap was adjusted to make the coating amount 170 g / m 2Forming a plate blank; placing the blank into a hot press, hot pressing at 115 DEG C, 1.3 MPa, hot pressing time per millimeter of plate thickness x 1.2 min; S5, naturally cooling the plate blank to room temperature for 2.5 h, sanding with 120 and 240 mesh step sandpaper, sanding to a surface roughness Ra≤1.6 μm, obtaining a high flame-retardant plate.

[0029] Example 4, preparing modified polyvinyl alcohol, the specific preparation steps are as follows: A1, taking 15 g of polyvinyl alcohol powder into a three-necked flask, then adding 150 mL of deionized water, placing in a 70 DEG C constant temperature water bath, stirring at 300 rpm for 40 min until the polyvinyl alcohol is completely swollen; then adding 0.5 g of sodium dodecyl sulfate, continuing to stir at 300 rpm for 20 min; then slowly adding 3 mL of glacial acetic acid with a rubber head dropper, stirring while adding, adjusting the pH value of the system to 5.5, stirring for 15 min to obtain a pretreated polyvinyl alcohol solution; A2, under the condition of 300 rpm stirring, adding 5 mL of ethylene glycol to the pretreated polyvinyl alcohol solution, stirring for 10 min, then adding a total of 2 mL of glutaraldehyde in 3 times, each time after adding interval 5 min, adjusting the water bath temperature to 50 DEG C, keeping 250 rpm speed for continuous stirring for 40 min, completing the condensation crosslinking reaction, turning off the water bath heating, and naturally cooling the solution to room temperature; A3, under the condition of 300 rpm stirring, adding 1 mL of titanate coupling agent to the reaction system after the second modification, stirring for 15 min; then adding 2 g of nano calcium carbonate, increasing the stirring speed to 400 rpm, and continuously stirring at room temperature for 30 min to obtain modified polyvinyl alcohol.

[0030] Example 5, preparing modified borax, the specific preparation steps are as follows: B1, taking 8 g of borax and dissolving in 80 mL of distilled water, placing in a 50 DEG C constant temperature water bath, stirring at 200 rpm until the borax is completely dissolved, keeping the temperature and stirring speed after dissolving for 30 min to make the borax fully hydrolyzed; then slowly adding 6 mL of glycerol, adjusting the stirring speed to 250 rpm, continuously stirring at 50 DEG C water bath for 50 min to complete the esterification reaction, and naturally cooling to room temperature; B2, adding 1.5 g of tartaric acid to the reaction system after the first modification, stirring at 250 rpm for 15 min; then adding a total of 1 g of citric acid in 2 times, each time after adding interval 10 min, keeping 250 rpm speed after all adding to continue stirring for 30 min to form a chelate structure; B3, under the condition of stirring at 300 rpm, 3 mL of polyethylene glycol was added into the second modified system, and stirred for 20 min; then 0.5 g of hydroxypropyl methyl cellulose was added, and stirred at 300 rpm for 40 min at room temperature to obtain the modified borax.

[0031] Comparative Example 1, a high flame-retardant board was prepared, and the specific preparation steps were as follows: The remaining steps were unchanged, only the modified polyvinyl alcohol of Example 3 was replaced with polyvinyl alcohol without any treatment, and a high flame-retardant board was prepared.

[0032] Comparative Example 2, a high flame-retardant board was prepared, and the specific preparation steps were as follows: The remaining steps were unchanged, only the modified borax of Example 3 was replaced with borax without any treatment, and a high flame-retardant board was prepared.

[0033]

[0034] According to the performance test results, the high flame-retardant boards of Examples 1-3 were superior to Comparative Examples 1 and 2 using unmodified polyvinyl alcohol and unmodified borax in terms of limiting oxygen index (32.5-33.8), vertical burning grade (all reaching V-0), bending strength (18.6-19.8 MPa), flexural modulus (3.2-3.5 GPa), heat distortion temperature (135-142℃), and other indicators, and had lower water absorption thickness expansion rate (1.7-2.1%), showing more excellent flame retardancy, mechanical properties, heat resistance and water resistance.

[0035] The above is only an example and description of the present application, and those skilled in the art can make various modifications or supplements to the described specific embodiments or use similar ways to replace, as long as they do not deviate from the invention or exceed the scope defined by the present claims, and should belong to the protection scope of the present application.

Claims

1. A high flame retardant panel, characterized by: The high-flame-retardant board comprises the following raw materials in parts by weight: 90-110 parts of magnesium oxide, 15-20 parts of magnesium chloride, 30-35 parts of magnesium sulfate, 1.5-3 parts of modified polyvinyl alcohol, 1-2 parts of starch, 0.3-0.8 parts of modified borax, 0.2-0.5 parts of silane coupling agent KH-550, 1-2 parts of anhydrous ethanol, 2.5-3.5 parts of nano zinc borate, 2-4 parts of chlorinated paraffin-70, 0.5-1 part of nano titanium dioxide, 5-10 parts of basalt fiber, 0.2-0.5 parts of calcium stearate, and 90-110 parts of deionized water.

2. A high flame retardant panel according to claim 1, characterized in that: The basalt fiber has a length of 3-5 mm and a diameter of 10-15 μm.

3. The high flame retardant board of claim 1, wherein: The modified polyvinyl alcohol is prepared according to the following steps: A1, polyvinyl alcohol powder is taken into a three-necked flask, deionized water is added, and the mixture is placed in a 70℃ constant-temperature water bath and stirred at a speed of 300 rpm for 40 min until the polyvinyl alcohol is completely swelled; then sodium dodecyl sulfate is added, and stirring is continued at a speed of 300 rpm for 20 min; then glacial acetic acid is slowly added dropwise with a rubber bulb dropper, and the pH value of the system is adjusted to 5.5 while stirring, and a pretreated polyvinyl alcohol solution is obtained after stirring for 15 min; A2, under the condition of stirring at a speed of 300 rpm, glycol is added to the pretreated polyvinyl alcohol solution, stirring is continued for 10 min, then glutaraldehyde is added in three portions with an interval of 5 min between each addition, the water bath temperature is adjusted to 50℃, stirring is continued at a speed of 250 rpm for 40 min, and the condensation crosslinking reaction is completed, the water bath heating is turned off, and the solution is naturally cooled to room temperature; A3, under the condition of stirring at a speed of 300 rpm, titanate coupling agent is added to the reaction system after the second modification, stirring is continued for 15 min; then nano calcium carbonate is added, the stirring speed is increased to 400 rpm, and stirring is continued at room temperature for 30 min to obtain modified polyvinyl alcohol.

4. A high flame retardant panel according to claim 3, characterized in that: In A1, the amount ratio of polyvinyl alcohol powder, deionized water, sodium dodecyl sulfate and glacial acetic acid is 15 g:150 mL:0.5 g:3 mL; wherein the polyvinyl alcohol is type 1788; In A2, the amount ratio of glycol and glutaraldehyde is 5 mL:2 mL; In A3, the amount ratio of titanate coupling agent and nano calcium carbonate is 1 mL:2 g.

5. The high flame retardant panel according to claim 1, wherein: The modified borax is prepared according to the following steps: B1, borax is dissolved in distilled water, and the mixture is placed in a 50℃ constant-temperature water bath and stirred at a speed of 200 rpm until the borax is completely dissolved, the temperature and stirring speed are maintained after the dissolution, and stirring is continued for 30 min to hydrolyze the borax; then glycerol is slowly added, the stirring speed is adjusted to 250 rpm, and stirring is continued at a 50℃ water bath for 50 min to complete the esterification reaction, and the mixture is naturally cooled to room temperature; B2, tartaric acid is added to the reaction system after the first modification, stirring is continued at a speed of 250 rpm for 15 min; then citric acid is added in two portions with an interval of 10 min between each addition, stirring is continued at a speed of 250 rpm for 30 min after the addition of all the citric acid, and a chelate structure is formed; B3, under the condition of 300 rpm stirring, polyethylene glycol was added into the second modified system, and stirred for 20 min; then hydroxypropyl methyl cellulose was added, and stirred at 300 rpm for 40 min at room temperature to obtain modified borax.

6. A high flame retardant panel according to claim 5, characterized in that: The amount ratio of borax, distilled water and glycerol in B1 is 8 g:80 mL:6 mL; The amount ratio of tartaric acid and citric acid in B2 is 1.5 g:1 g; The amount ratio of polyethylene glycol and hydroxypropyl methyl cellulose in B3 is 3 mL:0.5 g.

7. A high flame retardant panel according to claim 5, characterized by: The citric acid in B2 is added in several times, and combined with tartaric acid to form chelate structure, which ensures the thermal stability and flame retardant synergistic effect of borax.

8. A process for the production of high flame retardant board material, characterized by: Specifically comprising the following steps: S1, silane coupling agent KH-550 and anhydrous ethanol were added into a container, stirred at 1300 rpm for 15 min, and stood for 30 min for standby; 80-90℃ deionized water was taken and added into the modified borax to be stirred until dissolved, then poured into the above-mentioned silane coupling agent diluent, stirred at 300 rpm in 60-70℃ water bath for 15-20 min, and cooled for standby; deionized water was taken and added into a batching tank, stirred at 150 rpm and heated to 30-40℃, first added magnesium sulfate and stirred for 5 min, then added magnesium chloride, after adding, adjusted to 200 rpm and stirred for 25-35 min, until the salts were completely dissolved, to ensure that the salinity of the magnesium chloride and magnesium sulfate salt compound water was between 22-28 degrees, then stood for 15 min to release the bubbles, sealed the batching tank, and standby; S2, deionized water was poured into a reaction kettle, heated to 60-70℃ under 200 rpm stirring, and slowly added modified polyvinyl alcohol, continuously stirred until completely dissolved; starch and deionized water were mixed, stirred at 400 rpm for 10-15 min to make starch paste, poured into the above-mentioned solution, and stirred at 250 rpm for 30 min to obtain organic modified glue solution; S3, dry magnesium oxide, nano zinc borate, chlorinated paraffin-70, nano titanium dioxide, basalt fiber and calcium stearate were added into a double-shaft stirring mixer, dry mixed at 300 rpm for 3-5 min; the organic modified glue solution prepared in S2, the salt compound water agent prepared in S1 and the pretreatment solution in S1 were added, and stirred at 200-300 rpm for 30-40 min until the slurry was uniform and no particles, and the remaining deionized water was used to adjust the slurry viscosity to 2000-3000 cP; S4, put the slurry on the coating machine conveyor belt, adjust the gap to make the coating amount 165-175 g / m 2 Form the plate blank; put the blank into the hot press, hot press under the condition of 110-120 ℃, 1.2-1.5 MPa, the hot pressing time is every millimeter of plate thickness x 1.2 min; S5, the plate blank was naturally cooled to room temperature for 2-3 h, and sanded with 120 and 240 mesh step sandpaper, and sanded to a surface roughness Ra≤1.6 μm to obtain high flame retardant plate.

9. The process for producing a high flame-retardant board according to claim 8, characterized in that: The hot pressing process in S4 uses a temperature of 110-120℃ and a pressure of 1.2-1.5 MPa, and controls the hot pressing time to be per millimeter plate thickness×1.2 min, so that a dense structure is formed in the plate, and the uniform distribution of flame retardant components is ensured, thereby obtaining excellent flame retardant performance and dimensional stability.

Citation Information

Patent Citations

  • Preparation method of organic montmorillonite-modified polyvinyl formal sponge

    CN105175591A

  • Re-dispersible emulsion powder and its production

    JP2000053711A

Cited By

  • Fireproof coating and preparation method thereof

    CN121779984A